The aesthetics of Japanese fascism - Tansman, Alan (University of California Press, 2009)
In this study of Japanese cultural expression, Alan Tansman reveals how a particular, often seemingly innocent aesthetic sensibility helped create an 'aesthetic of fascism' in the years leading up to World War II.
10.1525/california/9780520245051.001.0001
Keywords: Kultur; Faschismus; Literatur; Gewaltdarstellung; Japanese literature; Fascism in literature; Fascist aesthetics; Fascism